THE QUALITY OF GOVERNMENT FINANCIAL REPORTS - Hendra Raza; Ratih Purwasih; Rico Nur Ilham (CV. Radja Publika, 2025)
This study aims to test the influence of the use of Big Data, Effectiveness of Budget Planning and Internal Control Systems Quality of Financial Reports in SKPD of Southeast Aceh Regency. Type The research uses a quantitative methodology approach. The population in This research is the SKPD of Southeast Aceh Regency, namely 34 SKPK. The in this study consisted of respondents from 34 SKPK. In the drawing The autho`s sample uses the Saturated Sampling technique, namely the technique for determining sample when all members of the population are used as samples. The data that obtained from primary data in the from of questionnaires. The results of this study with using the partial test (t) shows that the Big Data Usage Variable, The Effectiveness of Budget Planning and Internal Control Systems has an impact positive towards the quality of the Financial Report of the Southeast Aceh Regency SKPD.